Posttraumatic Stress Symptoms among Obstetricians with Personal Experience of Birth Trauma - Whelan, Anna R.; Griffin, Laurie B.; Russo, Melissa L.; Ayala, Nina K.; Miller, Emily S.; Clark, Melissa A. (American Journal of Perinatology, 2024)
Psychological birth trauma (BT), defined as an event that occurs during labor and delivery involving actual or threatened harm or death to the pregnant person and/or their baby, has been reported in up to one-third of births. Obstetrician-Gynecologists (OBGYNs) who personally experience BT are at a unique risk of re-traumatization upon return to work. We aimed to investigate the prevalence of personal BT among obstetricians and their perceptions of how personal BT impacts their experience of caring for obstetric patients.We performed a web-based survey of OBGYNs who had given birth. Participants were recruited from the “OMG (OBGYN Mom Group)” on Facebook. The questionnaire assessed individuals' personal experience of childbirth using items adapted from the “City Birth Trauma Scale” to assess posttraumatic symptoms related to their childbirth and patient interactions following the personal experience of BT. Responses were categorized by whether or not the participant considered one or more of their own births to be traumatic. Posttraumatic stress symptoms (PTSSs) and symptoms of occupational re-traumatization were compared by reported BT. Bivariable analyses were used.Of the 591 OBGYNs who completed the survey, 180 (30.5%) reported experiencing BT. Ninety-two percent of OBs cared for birthing patients after giving birth. There were no differences in demographic or clinical practice characteristics between those with and without BT. OBGYNs with BT experienced PTSSs including flashbacks (60.6 vs. 14.4%), amnesia (36.7 vs. 20.9%), and insomnia (24.4 vs. 1.2%) at higher rates than those without BT (p < 0.001).Almost one-third of OBGYNs in this sample reported personally experiencing BT, mirroring data from reported BT rates in the general population. Given that OBGYNs are at high risk for occupational re-traumatization, initiatives focused on improving support for birthing OBGYNs upon returning to work should be studied to assess the impact on emotional wellness among practicing OBGYNs.
Keywords: birth trauma; psychological birth trauma; OBGYN wellbeing; posttraumatic stress symptoms; occupational retraumatization